THE EFFECT OF PAIR CHECK TECHNIQUE AND PRIOR KNOWLEDGE ON STUDENTS WRITING SKILL AT SMAN 1 BANGKINANG - Nurhidayah Sari (Journal of English Language and Education, 2016)
This article was written to describe the study of the effect of the use of techniques pair check and initial knowledge of students on their writing skills in SMAN 1 Bangkinang that can be used as an alternative solution to the inaccuracy of the techniques used by teachers in teaching. The research is experimental penelitianquasi with a 2x2 factorial design, with cluster random sampling techniques. Acquisition datadari test prior knowledge and writing skills were analyzed by t-test and two-way ANOVA. The results showed that (1) the learning outcomes of students who were taught with techniques pair check is higher than the learning outcomes of students who are taught the technique of individual check, (2) students with prior knowledge of high-taught with techniques pair check to get a better result than in students are taught the technique of individual check, (3) students with prior knowledge Low taught the technique of pair check get better results than students taught by using the individual check, (4) there is no interaction between the two techniques and knowledge early on skills write.